Ecotourism Strategy in Facing the New-Normal Era (Case Study: Ecowisata Gunung Anyar) - Wiwik Dwi Susanti; Muchlisiniyati Safeyah; Fairuz Mutia (Nusantara Science and Technology Proceedings, 2020)
The COVID-19 pandemic has changed all aspects of life including people's habits of traveling and traveling. People limit themselves to mobilization to avoid spreading the virus. But that does not mean tourist attractions do not have the opportunity to rise again during the new normal era. According to the Director of the Indonesia Ecotourism Network, Ary Suhandi, in the new normal era, the trend of large numbers of tourism (mass tourism) is predicted to be replaced by the trend of quality tourism. "Ecotourism, adventure, and wellness tourism are great opportunities (travel.detik.com). So, that serious effort is needed by ecotourism managers to take advantage of these opportunities. The strategy carried out by the management must continue to prioritize the principles of health protocol handling covid 19. So that will provide comfort for visitors and managers. Ecotourism Gunung Anyar is one of the ecotourism in the East of Surabaya City which is back active in the new normal era. Various kinds of strategies are carried out by ecotourism Gunung Anyar to survive during the COVID-19 pandemic conditions. discussing Gunung Anyar's ecotourism strategy in facing the new normal era but still prioritizing the concept of conservation and education. This study uses qualitative and quantitative methods. Based on the results of the study it can be concluded that the strategy carried out includes internal and external strategies. The manager's efforts to continue to prioritize the concept of conservation, while externally are related to service strategies to visitors during the new normal.